Oral rehydration therapy - Avery, Mary Ellen (The Turkish Journal of Pediatrics, 1986)
In a lecture presented at the XXXth Congress of the Turkish National Pediatric Society in March 1986 in Ankara, the author describes how oral rehydration therapy, a practice which was first used by health workers in the lesser developed areas of the world, has proved itself and been adopted by physicians even in highly sophisticated hospitals of the "developed" world.
Keywords: oral rehydration therapy; diarrhea; USA; developed country